2021
DOI: 10.1186/s12884-021-04281-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel laparoscopic surgery for the repair of cesarean scar defect without processing scar resection

Abstract: Background Cesarean scar defect (CSD), especially CSD with residual myometrium less than 3 mm is reported to be the highest risk agent associated with uterine rupture for subsequent pregnancy. Currently, laparoscopic resection and suture was the mainstay therapy method for CSD with a residual myometrium less than 3 mm in women with a desire to conceive. Besides, the women have CSD related symptoms, especially postmenstrual bleeding, should be recommended for CSD treatment. This study is to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…The relative risk of PAS was 8.8 (95% CI: 6.1–12.6) for previous CS, 6.6 (95% CI: 4.4–9.8) for a single CS, 7.4 (95% CI: 4.4–9.8) for two CS, and 55.9 (95% CI: 25.0–110.3) for a history of three or more CS ( 45 ). The process of uterine tissue repair after CS is often accompanied by decreasing endometrial glands, inhibition of myometrial smooth muscle cell growth, excessive collagen fiber deposition, and massive leukocyte infiltration, which leads to long-term and chronic inflammation and scarring ( 63 ). There appears to be preferential attachment of the blastocyst to the scar site, which may be associated with defective decidua in that region, resulting in abnormal implantation ( 64 ).…”
Section: Approaches To Establish the Pas Modelmentioning
confidence: 99%
“…The relative risk of PAS was 8.8 (95% CI: 6.1–12.6) for previous CS, 6.6 (95% CI: 4.4–9.8) for a single CS, 7.4 (95% CI: 4.4–9.8) for two CS, and 55.9 (95% CI: 25.0–110.3) for a history of three or more CS ( 45 ). The process of uterine tissue repair after CS is often accompanied by decreasing endometrial glands, inhibition of myometrial smooth muscle cell growth, excessive collagen fiber deposition, and massive leukocyte infiltration, which leads to long-term and chronic inflammation and scarring ( 63 ). There appears to be preferential attachment of the blastocyst to the scar site, which may be associated with defective decidua in that region, resulting in abnormal implantation ( 64 ).…”
Section: Approaches To Establish the Pas Modelmentioning
confidence: 99%
“…The second point is how to suture the uterine myometrium after resection. Several authors performed double‐layer sutures, 53,65,71,74,75,78,82,85,90,94 whereas several authors performed single‐layer sutures 76,79–81,89,91,95 . So far, no papers compare the superiority of single‐layer and double‐layer sutures for CSD repair.…”
Section: Laparoscopic Surgery In Women With Csdimentioning
confidence: 99%
“…Zhang et al demonstrated that the surface of the uterine serosa was condensed by vertical suturing without CSD removal 88 . Zhang et al 91 also demonstrated that laparoscopic repair without scar resection is feasible, safe, and effective for AUB by comparing resection procedures. Peng et al 92 demonstrated that both folding and muscle flap filling suture techniques are effective and safe in women with CSDi.…”
Section: Laparoscopic Surgery In Women With Csdimentioning
confidence: 99%
See 2 more Smart Citations